Η χρήση του near field communication σε καθημερινές δραστηριότητες - Ζαβρός, Φάνος (Τμήμα Επικοινωνίας και Σπουδών Διαδικτύου, Σχολή Επικοινωνίας και Μέσων Ενημέρωσης, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
This thesis entitled “The use of Νear Field Communication in Daily Activities” was developed by Fanos Zavros, student of the Department of Communication and Internet Studies of Cyprus University of Technology during the 8th semester, under the supervision of Lecturer Prof. Lambros Lambrinos and it was completed in May 2014. This thesis presents a system, which focuses on the communication, between a mobile device and various objects (eg a book) or a sensor (eg a machine payments) through Near Field Communication (NFC) technology. The system of the present study will be adapted to the daily needs of students, and the goal was to implement a reliable and automated way that will help mainly the needs of students and the university. Thus, it was designed in a way which students will replace traditional measures, such as taking class attendance, purchase items from the cafeteria, borrow books from the library, etc. with the benefits of this technology using a device which they always carry with them, their smartphone. The thesis was quantitative but experimental too. Thus the methodology used in this study has to do with the implementation and development of the system and its design. It used a modified model of the traditional software development model (the “waterfall model”) that requires careful system design to avoid potential problems before implementation. The integrated solution designed for this system could not be completed during the time frames of this thesis and was therefore decided to implement only a part of that system. So, during the tests an automated system was developed, whereby students can take attendances from mobile phones running the Android operating system, touching it at a sensor at the entrance of the classroom. Access to control and monitor the attendances have the professor of the course through a website. That was implemented so the professor can view the presences per student or class.
Keywords: Near Field Communication; Internet; Android; Mobile phone; Επικοινωνία Κοντινού Πεδίου; Διαδίκτυο; Κινητό τηλέφωνο